Investigation of the effects of pinealectomy on acetylcholinesterase enzyme activity and oxidative stress in rat brain - Pekmez, Hidir; Ozkaya, Ahmet; Uckun, Mirac; Zayman, Emrah; Aydin, Merve; Canpolat, Sinan; Gul, Mehmet (Springer Japan Kk, 2025)
The pineal gland releases melatonin to regulate our body's circadian rhythm based on light and dark cycles. The pinealectomy (PINX) model is an experimental approach employed to investigate the potential impact of melatonin on various tissues and pathologies. In this study, acetylcholinesterase (AChE) enzyme activity levels, oxidative stress parameters, histopathological findings, and serum melatonin levels in rat brain tissue were evaluated following pinealectomy. 24 male Sprague Dawley rats were randomly divided into groups: control, Sham-Pinealectomy (SHAM), and PINX. Brain tissue samples were taken at the end of a 50-day experimental period to determine the parameters of AChE, glutathione s-transferase (GST), carboxylesterase (Ces) enzyme activities, and malondialdehyde (MDA), reduced glutathione (GSH) levels spectrophotometrically. Moreover, serum melatonin levels were measured, and tissues underwent standard histological analysis to determine the histopathological damage score. In this study, we found that the PINX group had decreased AChE and Ces enzyme activity, increased MDA, decreased GSH levels, and no change in GST enzyme activity. A relative decrease in serum melatonin levels was also observed in the PINX group. In the light microscopic examination of the brain tissue of pinealectomy rats, it was observed that the eosinophilic staining intensity increased, heterochromatic/pycnotic-looking neuron nuclei were prominent in the cortex layers and hippocampus, and perineural edematous areas were abundant. Excessive perineuronal edema, cytoplasmic eosinophilia, and heterochromatic/pycnotic nuclei were found based on the histopathological damage score. After pinealectomy, we observed an increase in oxidative stress and a decrease in AChE levels in the brain.
Keywords: Pinealectomy; AChE; Oxidative stress; Melatonin